Peningkatan Pengetahuan Pencegahan Covid-19 Melalui Edukasi Pentingnya Gizi Seimbang Pada Mahasiswa Tingkat II STIKES RS. Baptis Kediri - Erva Elli Kristanti; Yoyok Febrijanto (Pelita Medika, 2021)
Background : Along with the continued increase in the Covid-19 outbreak, health protocols must still be carried out considering that many activities can pose a risk to close family. In addition, the need to consume a balanced diet strongly supports the body's immunity in preventing the risk of contracting Covid-19. Therefore, education about health protocol behavior, healthy lifestyle, frequent hand washing and not forgetting to consume balanced nutrition needs to be continuously improved. Method : This service activity aims to increase knowledge about balanced nutrition to prevent covid-19 in STIKES RS students. Kediri Baptist. This service activity is carried out by providing online questionnaires and booklet educational media to students and then evaluating knowledge again to obtain nutritional knowledge for the prevention of COVID-19 properly. Results : The results of the service activities showed that there was an increase in knowledge before as many as 18 students (94.7%) had sufficient knowledge, and after education 18 students (94.7%) were good, with a p value analysis of 0.000. Conclusion : Balanced nutrition education provides increased knowledge to students of STIKES RS. Baptist Kediri